Pharmacognosy Determination and in vitro Antioxidant, Anti-Inflammatory, Antimycobacterial Activity of Salt Marsh Plants: Sesuvium portulacastrum and Salicornia brachiata - Venkatraman, Anuradha (Journal of King Abdulaziz University: Marine Sciences, 2022)
Mangroves are trees or large shrubs which have special adaptations to survive in this environment and grow within the intertidal zone in tropical and subtropical regions. Sesuvium portulacastrum (seapurslane) is, herbaceous, perennial, dichotomous, halophyte fast growing plant that belongs to family Aizoaceae. Salicornia brachiata Roxb, is a halophyte, commonly known as sea asparagus widely used as food item in several countries. Then, In vitro studies like, antioxidant, anti-inflammatory and antimycobacterial assay was carried out. The IC50 values of Salicornia brachiata and Sesuvium portulacastru was found to be 288.166, 369.451 and 369.764 µg/ml for DPPH scavenging activity. The presence of various primary and secondary metabolites was revealed in the present study. It also showed the better in vitro activities and was the most active plants against MDRTB, MTB and H37RV strain. This study validates the medicinal use of plants in the treatment of TB which have promising effect against MDRTB, MTB and H37RV.